Impact of "+Contigo" training on the knowledge and attitudes of health care professionals about suicide - José Carlos Santos; Rosa Maria Pereira Simões; Maria Pedro Queiroz de Azevedo Erse; Jorge Daniel Neto Façanha; Lúcia Amélia Fernandes Alves Marques (Universidade de São Paulo, 2014)
OBJECTIVES: to evaluate the results of "+Contigo" training, developed by nurses and directed at 66 health professionals of integrated school health teams in Primary Health Care.METHOD: quantitative with data collection through the Suicide Behavior Attitude Questionnaire, administered before and after the training.RESULTS: significant increases were observed in suicide prevention knowledge and in changing attitudes of health professionals towards individuals with suicidal behavior.CONCLUSION: these results allow us to affirm that nurses hold scientific and pedagogical knowledge that grant them a privileged position in the health teams, to develop training aimed at health professionals involved in suicide prevention.